Інтелектуалізовані сіткові моделі технологічних процесів у фармацевтиці - Шпіт, О. С.; Ямпольський, Л. С.; Лісовиченко, О. Т. (Видавництво Державного університету "Львівська політехніка", 2000)
In this article, approaches to construction of intelligent Petri net-based models of Flexible Automation Lines (FAL) are considered and a technique for their implementation is proposed. Modified Petri nets are applied to the synthesis of FAL process models.